Transarterial Onyx embolization of jugular foramen dural arteriovenous fistula with spinal venous drainage manifesting as myelopathy—a case report and review of the literature - Jin, Hengwei (Interv Neuroradiol, 2016)
We report a rare case of jugular foramen dural arteriovenous fistula (DAVF) with spinal venous drainage. A 48-year-old woman suffered from progressive weakness of lower extremities and incontinence of urine and feces for 14 days. Magnetic resonance imaging (MRI) revealed a tortuous posterior medullary vein at C2–T2 and ischemic signal at C2–C4 of the spinal cord. Brain MRI revealed an abnormal high signal near the left jugular foramen. Digital subtraction angiography of the spinal vascular was negative, while brain angiography showed a left jugular foramen DAVF with spinal perimedullary venous drainage. The patient recovered completely soon after endovascular embolization with Onyx-18. Diagnosis of a DAVF presenting with myelopathy is challenging. Early diagnosis and treatment are essential for a favorable outcome.